Nanoparticle-Mediated Interleukin-12 Cancer Gene Therapy - Hallaj-Nezhadi, S.; Lotfipour, F.; Dass, Crispin (Canadian Society for Pharmaceutical Sciences, 2010)
Interleukin-12 (Il-12) is a heterodimeric cytokine which has been proven to possess antitumor effects in various animal models via stimulating the immune system. However, the main problem associated with Il-12 protein delivery is its instability as well as cytotoxicity subsequent to systemic administration in rodents and in clinical trials. However, gene delivery can be used to deliver genes of interest to the tumor site. Hence, a large number of studies have been undertaken to deliver genes of interest to the tumor site through viral or non-viral vectors. Viral DNA delivery systems suffer from safety concern due to the toxicity of the viruses and strong immune response, while non-viral gene delivery systems proffer lower transfection efficiency. In contrast, nanometer-sized complexes of therapeutic DNA may prove to be more efficient for administration of therapeutic genes to solid tumors compared to administration of naked plasmid DNA. Nanoparticle-based gene delivery systems might be more pertinent, due to enhanced tissue penetrability, and improved cellular uptake. Il-12 gene delivery has already been reported with different nanoparticles containing DNA. This article provides a review on the in vivo and in vitro studies using various nanoparticles, for delivery of the Il-12 gene to neoplastic cells. The future of these promising approaches lies in the development of better techniques for preparing Il-12 gene delivery systems with complete efficiency of viral vectors in addition to the highest safety for cancer patients.